The Financial Accelerator: Evidence from International Housing Markets - Almeida, Heitor; Campello, Murillo; Liu, Crocker (Review of Finance, 2006)
Abstract This paper shows novel evidence on the mechanism through which financial constraints amplify fluctuations in asset prices and credit demand. It does so using contractual features of housing finance. Among agents whose housing demand is constrained by the availability of collateral, those who can borrow against a larger fraction of their housing value (achieve a higher loan-tovalue, or LTV, ratio) have more procyclical debt capacity. This procyclicality underlies the financial accelerator mechanism. Our study uses international variation in LTV ratios over three decades to test whether (a) housing prices and (b) demand for new mortgage borrowings are more sensitive to income shocks in countries where households can achieve higher LTV ratios. The results we obtain are consistent with the dynamics of a collateral-based financial accelerator in international housing markets.